1994
DOI: 10.1002/jlb.56.3.389
|View full text |Cite
|
Sign up to set email alerts
|

The neuropathogenesis of HIV-1 infection

Abstract: HIV infection in brain revolves around productive viral replication in cells of mononuclear phagocyte lineage, including brain macrophages, microglia, and multinucleated giant cells [1-4]. Together, they are the investigators for cellular and viral neurotoxic activities [5-10]. Several published reports show that viral and/or cellular products produced from HIV-1-infected macrophages injure neurons and induce glial proliferation during advancing central nervous system (CNS) infection [11-18]. These findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
129
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(133 citation statements)
references
References 49 publications
2
129
0
2
Order By: Relevance
“…These resident macrophages of the brain are the ontogenetic and functional equivalent of macrophages in somatic tissues (29). Histopathological evidence suggests that microglia play an important role in the neuropathogenesis of HIV-1 infection within the CNS (30)(31)(32)(33). Permissive HIV-1 infection of the CNS occurs only in microglia, although astrocytes are also involved in HIV-1-related neuropathogenesis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…These resident macrophages of the brain are the ontogenetic and functional equivalent of macrophages in somatic tissues (29). Histopathological evidence suggests that microglia play an important role in the neuropathogenesis of HIV-1 infection within the CNS (30)(31)(32)(33). Permissive HIV-1 infection of the CNS occurs only in microglia, although astrocytes are also involved in HIV-1-related neuropathogenesis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, still no cure for the catastrophic consequence of SCI in paralyzed patients. Gendelman and Tardieu (15) have shown that trauma of the mature CNS leads to hypoxia-induced angiogenesis and infiltration of activated brain macrophages and neutrophils, all of which leads to scarring (16,17). Gliosis, the formation of a scar in injured CNS, involves hypoxia-driven inflammatory angiogenesis (18,19).…”
mentioning
confidence: 99%
“…Gliosis, the formation of a scar in injured CNS, involves hypoxia-driven inflammatory angiogenesis (18,19). Gliosis includes proliferation of astrocytes and microglia, and inflammatory infiltration of peripheral macrophages (15)(16)(17). CM101 is an antipathoangiogenic polysaccharide (20) derived from group B streptococcus (GBS) (21) that inhibits angiogenesis and subsequent infiltration of inflammatory cells and thereby formation of granulation tissue, which produces scarring (M. Neeman, R. Abramowitch, B.D.W., and C.G.H., unpublished data).…”
mentioning
confidence: 99%
“…A recent study has shown that VIP can also prevent a similar NMDA-induced, nitric oxide-dependent injury in lung tissue (63). Elevated levels of quinolinate (64,65) and toxic products (including cytokines) released from macrophages/microglia have also been associated with increased levels of gp120 and may play a role in gp120 toxicity (55,59,60,66,67).…”
Section: Discussionmentioning
confidence: 99%